Slow Gait Speed and Risk of Mortality or Hospital Readmission After Myocardial Infarction in the Translational Research Investigating Underlying Disparities in Recovery from Acute Myocardial Infarction: Patients' Health Status Registry - Dodson, John A.; Arnold, Suzanne V.; Gosch, Kensey L.; Gill, Thomas M.; Spertus, John A.; Krumholz, Harlan M.; Rich, Michael W.; Chaudhry, Sarwat I.; Forman, Daniel E.; Masoudi, Frederick A.; Alexander, Karen P. (Journal of the American Geriatrics Society (JAGS), 2016)
Objectives To determine the prognostic value of slow gait in predicting outcomes 1 year after acute myocardial infarction (AMI). Design Observational cohort with longitudinal follow‐up. Setting Twenty‐four U.S. hospitals participating in the Translational Research Investigating Underlying disparities in recovery from acute Myocardial infarction: Patients' Health status Registry. Participants Older adults (≥65) with in‐home gait assessment 1 month after AMI (N = 338). Measurements Baseline characteristics and 1‐year mortality or hospital readmission adjusted using Cox proportional hazards regression in older adults with slow (<0.8 m/s) versus preserved (≥0.8 m/s) gait speed. Results Slow gait was present in 181 participants (53.6%). Those with slow gait were older, more likely to be female and nonwhite, and had a higher prevalence of heart failure and diabetes mellitus. They were also more likely to die or be readmitted to the hospital within 1 year than those with preserved gait (35.4% vs 18.5%, log‐rank P = .006). This association remained significant after adjusting for age, sex, and race (slow vs preserved gait hazard ratio (HR) = 1.76, 95% confidence interval (CI)=1.08–2.87, P = .02) but was no longer significant after adding clinical factors (HR = 1.23, 95% CI=0.74–2.04, P = .43). Conclusion Slow gait, a marker of frailty, is common 1 month after AMI in older adults and is associated with nearly twice the risk of dying or hospital readmission at 1 year. Understanding its prognostic importance independent of comorbidities and whether routine testing of gait speed can improve care requires further investigation.